Low Level Clouds Analysis Relating to Synoptic Weather Types at Bratislava Airport - Sandra Krollova (Communications - Scientific letters of the University of Zilina, 2014)
Low level clouds are one of the most important meteorological phenomena, which can significantly influence every flight phase. In general, clouds are visible indicators of physical processes realized in the atmosphere. They provide information about winds, stability, moisture content and travelling weather systems. Knowledge of cloud base is very important, particularly to a pilot on the descent to an airport flying through a cloud. Cloud base is given as the height of the base of the cloud above a particular level (usually ground level). For aerodrome reports and forecasts the base is the height above the official aerodrome level. For international airports, reports should refer to the approach area; for airports equipped with ILS reference should be to the site of the Middle Marker beacon.This paper deals with analysis of diurnal and annual variations of low level clouds at the Slovak international airport in Bratislava. The results are applicable in aviation weather forecasting and characterizing of dynamic climate of the region.